The efficacy and safety of Xuebijing injection for corona virus disease 2019: A protocol for a systematic review and meta-analysis. Issue 49 (4th December 2020) - Fu, Jiaming; Wu, Lili; Ma, Yingying; Liang, Qun
Abstract: Background: Corona virus disease 2019 (COVID-19) is an epidemic respiratory infectious disease caused by Severe Acute Respiratory Syndrome Coronavirus 2 infection. Now it is popular all over the world on a large scale. COVID-19 has the characteristics of rapid transmission, atypical clinical symptoms, easy missed diagnosis and misdiagnosis, and so on. which has seriously affected social and economic development and people's health. Severe acute respiratory syndrome corona virus type 2 infection may lead to systemic cytokine storm, which leads to a sharp deterioration of the condition of ordinary patients. At present, no specific drug has been found in the clinical treatment of covid-19, while Xuebijing injection has been widely used in severe patients in China as a traditional Chinese medicine. The aim of this study is to assess the effificacy and safety of Xuebijing injection for COVID-19. Methods: Before the research, we conducted a comprehensive search on relevant websites. Two professional researchers will gradually screen, read the title, abstract and full text if necessary, and independently select qualified documents according to the inclusion and exclusion criteria. We will conduct a meta-analysis of the results related to COVID-19 to assess the risks of bias and data extraction. The heterogeneity of data will be studied by Cochrane X 2 and I 2 tests. The evaluation of publication bias will be carried out by funnel chart analysis and Eger test. Results: This review will be disseminated in print by peer-review. Conclusion: Our research is to scientifically analyze the clinical evidence of Xuebijing injection in treating severe COVID-19 patients.